Nutritional Status of School-Going Children Visiting Outdoor Patient Department of a Tertiary Care Hospital - Sohail Ashraf, Saba Mushtaq, Fatima Tuz Zahra,, Somayya Siddiqa, Quratulain, Nargis Bano, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the nutritional status of school-going children visiting the outdoor patient department of a tertiary care hospital. Study Design: Cross-sectional study Place and duration: Pediatric OPD of POF hospitalWah Cantt/ NUMS University from 1 June 2021 to 30 August 2021 Methodology: The age of each child was verified from the hospital HMIS data after which weight and height were recorded. Weight in kilograms (Kg) divided by the square of height in meters was used to determine body mass index. Using WHO AnthroCalc v 2.10, Z score values for weight for age, height for age, and BMI for age were determined. Results: In the present study, 51.6% were of male gender out of 519 children. Mean age was 9.2 (SD = ±2.2) years, 56.6% were of age less than 10 years old, mean height was 131.4 (SD=±14.8) cm and mean weight was 28.4 kg (SD=±10.9). 46.8% studied in government schools, 52.8% in private schools and just 0.4% in Madrasa. The majority i.e. 325 (62.5%) children were found with normal body mass index, 66(12.7%) were thin, 49 (9.4%) were of severe thinness, 48 (9.2%) were overweight and 31 (6%) were found obese according to the WHO BMI criteria for children. Conclusion: WHO BMI criteria is a valuable tool for the screening of malnutrition in children. Our study showed a double burden of malnutrition in school going children with high prevalence of obesity and severe thinness in boys. Keywords: Thinness, body mass index, double burden of malnutrition, obesity